The culture of high crime societies. Some preconditions of recent 'Law and Order' policies - Garland, David (The British journal of criminology, 2000)
In a continuing attempt to explain the emergence of new strategies of crime control in the UK and USA, a theory of cultural adaptation is developed. The paper argues that the political and policy shifts of recent years have been conditioned by prior changes that have occurred at the level of social structures and cultural sensibilities. A historical account of these changes is outlined, together with a characterization of the culture of high crime societies